Tapping the biosynthetic potential of marine Bacillus licheniformis LHG166, a prolific sulphated exopolysaccharide producer: structural insights, bio-prospecting its antioxidant, antifungal, antibacterial and anti-biofilm potency as a novel anti-infective lead - Alharbi, Nada K.; Azeez, Zahraa Falah; Alhussain, Haitham Mohammed; Shahlol, Aisha M. A.; Albureikan, Mona Othman I.; Elsehrawy, Mohamed Gamal; Aloraini, Ghfren S.; El-Nablaway, Mohammad; Khatrawi, Elham Mohammed; Ghareeb, Ahmed (Frontiers in Microbiology, 2024)
The escalating global threat of antimicrobial resistance necessitates prospecting uncharted microbial biodiversity for novel therapeutic leads. This study mines the promising chemical richness of Bacillus licheniformis LHG166, a prolific exopolysaccharide (EPSR2-7.22g/l). It comprised 5 different monosaccharides with 48.11% uronic acid, 17.40% sulfate groups, and 6.09% N-acetyl glucosamine residues. EPSR2 displayed potent antioxidant activity in DPPH and ABTS . + , TAC and FRAP assays. Of all the fungi tested, the yeast Candida albicans displayed the highest susceptibility and antibiofilm inhibition. The fungi Aspergillus niger and Penicillium glabrum showed moderate EPSR2 susceptibility.In contrast, the fungi Mucor circinelloides and Trichoderma harzianum were resistant. Among G+ve tested bacteria, Enterococcus faecalis was the most susceptible, while Salmonella typhi was the most sensitive to G-ve pathogens. Encouragingly, EPSR2 predominantly demonstrated bactericidal effects against both bacterial classes based on MBC/MIC of either 1 or 2 superior Gentamicin. At 75% of MBC, EPSR2 displayed the highest anti-biofilm activity of 88.30% against B. subtilis, while for G-ve antibiofilm inhibition, At 75% of MBC, EPSR2 displayed the highest anti-biofilm activity of 96.63% against E. coli, Even at the lowest dose of 25% MBC, EPSR2 reduced biofilm formation by 84.13% in E. coli, 61.46% in B. subtilis. The microbial metabolite EPSR2 from Bacillus Licheniformis LHG166 shows promise as an eco-friendly natural antibiotic alternative for treating infections and oxidative stress.